Neuroscience and Religion as the Basis for Character Education: : Aisyah Dahlan’s Perspective - Sari, Suci Mayang; Putra, Pristian Hadi (Belajea: Jurnal Pendidikan Islam, 2023)
This study analyses the integrative relationship between neuroscience, religion, and character typology as the foundation of character education from Aisah Dahlan’s perspective. The method used is content analysis with a literature approach, utilising primary sources from video content on the YouTube account @Aisah Dahlan. The results indicate that these three elements form a complementary foundation for character development. Neuroscience explains the physiological relationship between the brain, nervous system, and behavioural formation, with brain development reaching 90% by the age of 5. Religion provides a moral foundation and ultimate goal to shape individuals with noble morals in accordance with human nature (fitrah). Meanwhile, the character typology of phlegmatic, melancholic, choleric, and sanguine, which has existed since conception, helps in understanding the diversity of children’s personalities. The implication is that parents and educators need to understand the stages of a child’s brain development and their unique character typology to apply character education methods tailored to each child’s needs and conditions, thereby making the educational process more effective and optimal.